Development of an Orthanc Pacs-Based Radiology Information System (RIS) at The Ilyas Tarakan Type D Navy Hospital - Nofa Rosalina; Bambang Satoto; Rasyid Rasyid; Alfisna Fajru Rohmah (Syntax Corporation Indonesia, 2026)
Digital transformation in radiology management is urgently needed to improve accuracy, efficiency, and compliance with medical data retention standards. However, many type C and D hospitals in Indonesia still rely on paper- and film-based workflows because commercial Picture Archiving and Communication System (PACS) solutions are costly. This research aimed to design, develop, and evaluate an integrated Radiology Information System (RIS) based on the open-source Orthanc PACS at Ilyas Tarakan Naval Hospital, a type D hospital, to address radiology data fragmentation, limited Digital Imaging and Communications in Medicine (DICOM) storage on modality consoles, and paper-based reporting workflows. A Research and Development (R&D) approach was employed using the Rapid Application Development (RAD) model, consisting of a preliminary study, system development, expert validation through black-box testing, and limited pilot testing using a pre-test/post-test design involving ten respondents. The RIS was developed using Laravel and Bootstrap and integrated with Orthanc PACS through a Modality Worklist (MWL) mechanism. System performance was analyzed using normality, homogeneity, and Mann–Whitney statistical tests. Expert validation showed 100% validity across functionality, performance, user interface, security, compatibility, error handling, and usability aspects, while the integration aspect could not be evaluated due to hospital policy constraints. Pilot testing demonstrated a significant improvement in usability across all seven measured dimensions, with a Mann–Whitney test result of p = 0.000 (p < 0.05). The Orthanc-based RIS-PACS provided an effective and low-cost model for digitizing radiology services in budget-constrained type D hospitals and is recommended for gradual integration with the hospital information system.